Efficient Time Bars? A New Rationale for the Existence of Statutes of Limitations in Criminal Law - Listokin, Yair (The journal of legal studies, 2002)
This paper proposes a novel normative economic explanation for statutes of limitations for criminal offenses. Because potential criminals tend to discount the future at higher rates than society, punishing crimes long after they are committed will be inefficient. Punishments after a long lag have only a nominal deterrent effect, while they may cost society substantial sums. The model presented in the paper derives the optimal statute of limitations for a crime by modifying the standard model of public enforcement of law to consider lags between crime and punishment. In addition, numerical simulations of the model suggest that some U.S. statutes of limitations are generally consistent with optimal limitations (probably serendipitously). Finally, the paper employs the model to critique several tenets of the law concerning statutes of limitations